Models of Policy Implementation in Islamic School Learning Systems During Covid-19 - Muslim, Moh; Hasan, Nur; Ratih, Ika (Jurnal Pendidikan Agama Islam, 2021)
Covid-19 has had an impact on the management of learning. Principals must establish the right policies in dealing with COVID-19. The head of MTs Maarif NU Blitar City established an In-Out Learning System policy. The purpose of this study was to find out and elaborate on how the policy implementation model set by the head of MTs Maarif NU Blitar City in dealing with COVID-19. This research uses a qualitative approach with the type of case study research. Data were collected through observation, interviews, and documentation methods, data analysis was carried out using interactive methods which included the stages of data collection, condensation, data presentation, and drawing conclusions. The results of the research on the in-out learning system policy implementation model conducted by the head of MTs Maar NU Blitar City showed that there were five factors, namely, Oral and Written Communication (OCW), Tangible and Intangible Resources (TIR), Disposition process based on communication, positioning and incentives, Camouflage Bureaucratic Structure (CBS) and Leader and team commitment (LTC).